Electronic cigarettes in Italy: a tool for harm reduction or a gateway to smoking tobacco?. Issue 2 (18th January 2019) - Liu, Xiaoqiu; Lugo, Alessandra; Davoli, Enrico; Gorini, Giuseppe; Pacifici, Roberta; Fernández, Esteve; Gallus, Silvano
Abstract : Introduction: More than a decade after electronic cigarettes (e-cigarette) hit the European market, we are still debating whether they may help or hinder tobacco control. It is therefore useful to explore the potential net effect of e-cigarette use in the general population. Methods: We annually conduct a face-to-face survey on smoking in Italy on a representative sample of the general population aged 15 years or over (52.4 million). A total of 15 406 subjects were interviewed in 2014–2018. We investigated the consequences of using e-cigarettes on tobacco smoking behaviour among ever and regular e-cigarette users. Results: In all, 5.7% of our sample reported ever e-cigarette use. Multivariate analyses showed more use by men, ex-smokers and current smokers. E-cigarette use decreased with age and increased with education and calendar year. Only 1.1% of subjects were regular e-cigarette users. This prevalence rose from 0.4% in 2014–2015 to 1.8% in 2016–2017 and was 1.3% in 2018. Among 522 ever users, 13.2% stopped smoking after trying e-cigarettes and 22.2% started smoking or relapsed after using e-cigarettes. The corresponding estimates among regular users were 24.7% and 28.0%, respectively. Conclusions: Among Italian e-cigarette users, those (re)starting smoking after using e-cigarettes outnumber those who stop smoking after using e-cigarettes. From a public health point of view, e-cigarettes may have an unfavourable net effect. Consequently, if we are not able to prevent sales of e-cigarettes to non-smokers, this product will more likely stimulate smoking tobacco than reduce harm.